Politics of translation: A cosmopolitan approach. Issue 1 (2nd January 2017) - Bielsa, Esperança; Aguilera, Antonio
ABSTRACT: Translation has gained a central importance in recent accounts of cosmopolitanism that emphasise global interdependence and the interaction between different cultures and traditions. In this context, it becomes necessary to formulate a politics of translation that questions some idealist assumptions about translation that are present in the sociological literature, specifies translation as a fundamentally ethnocentric act, and formulates relevant strategies to confront this inherent ethnocentrism in order to open up translation to the difference of the other. This implies a broad conception of translation primarily as a social relation with foreignness, rather than merely as the transfer of meaning from one language into another. In this light, a politics of translation based on linguistic hospitality is seen as a more realistic alternative than Derrida's notion of absolute hospitality, while also responding to problems related to the difficulty of understanding, which are minimised in a Habermasian notion of tolerance. It also connects with a philosophy that relates language to its anthropological and material roots, thus presenting linguistic hospitality as a space where a human potential based on flexibility and adaptability can flourish.